A positive feedback loop bi-stably activates fibroblasts - So-Young Yeo (Nature Portfolio, 2018)
Normal adult tissue fibroblasts can be activated during wound healing, pathologic fibrosis and in cancer stroma, but the regulatory network that controls its dynamics is unknown. Here the authors show that fibroblasts are activated by a positive feedback loop formed by Twist1, Prrx1, and Tenascin-C bi-stably.